Defining and Evaluating a Novel Outcome Measure Representing End-Stage Knee Osteoarthritis: Data from the Osteoarthritis Initiative - Driban, Jeffrey B. (Clin Rheumatol, 2016)
OBJECTIVE: We described a definition of end-stage knee osteoarthritis (esKOA) and evaluated its association with health outcomes and osteoarthritis risk factors. METHOD: We included Osteoarthritis Initiative participants with or at-risk for knee osteoarthritis who had complete baseline data. We defined esKOA by adapting a validated appropriateness algorithm for total knee replacement based on data from baseline and the first 4 follow-up visits. We performed person-based analyses, including both knees from all participants. Participants met the definition of esKOA at the visit at which ≥1 knees reached the esKOA criteria. We assessed differences in individual characteristics between groups at baseline and over time; and tested if incident esKOA (outcome) was associated with osteoarthritis risk factors (e.g. age, maximum adult weight, quadriceps strength). RESULTS: The cohort consisted of 3916 participants with mean age of 61 (SD=9) years, and mean body mass index of 28.4 (4.7) kg/m(2); 59% were female, and 9.7% developed incident esKOA. Those with incident esKOA had poorer health outcomes at baseline and greater declines in health outcomes, with the exception of SF-12 mental health score. Five out of 9 tested risk factors were associated with incident esKOA in unadjusted analyses, with older age (≥65 years; odds ratio=1.44, 95% confidence interval=1.19 to 1.83) and quadriceps weakness (odds ratio=0.78, 95% confidence interval=0.71 to 0.86) remaining significant in adjusted models. CONCLUSIONS: Older age and quadriceps weakness predicted esKOA. esKOA is also characterized by poor health-related outcomes. This definition of esKOA could be a new clinically relevant outcome measure for osteoarthritis research.